The Role of ESG and Financial Performance in Enhancing Corporate Financial Flexibility in Indonesia - Rosmayanti, Rosmayanti (Jurnal Accounting Information System (AIMS), 2026)
This research was conducted to examine the influence of Environmental, Social, and Governance (ESG) performance and financial performance on financial flexibility. The object of the research is a company listed on the Indonesia Stock Exchange from 2022 to 2024 and has an ESG performance every year on the Thomson Reuters database. The research method used is quantitative with a correlational descriptive design. The analysis technique uses multiple linear regression. The results show that financial performance and ESG performance have a significant positive effect on financial flexibility. This indicates that ESG performance and financial performance can increase a company's financial flexibility. Therefore, to maintain and increase financial flexibility, companies need to pay attention to aspects of company performance, both non-financial performance in this case ESG and financial performance. This study is limited to companies that report ESG performance to Thomson Reuters, so for future research it can use other ESG performance indices such as the Bloomberg database  and the Dow Jones sustainability index.